Notes on the Image of Croatia and the Croats with the Romanians from Transylvania (1867-1914) - POPOVICI, Vlad (Studia Universitatis Babeș-Bolyai Historia, 2016)
Notes on the Image of Croatia and the Croats with the Romanians from Transylvania (1867-1914). The present study proposes to succinctly analyze the means of building an image of Croatia and Croats by the Romanians in Transylvania during the dualist period. Even though they were citizens of the same state, Croats rose, within Romanian press, and later in historical writings, a lot less interest than other nations in the Empire. This was both due to the limited direct interaction between the two nations, as well as the different political situation after 1867. Together with general geographical descriptions, the field of politics, social-cultural initiatives and the image of a people with martial attributes represented the main coordinates of the imagological construction within the Romanian press and school textbooks. The image is a generally positive one, showing even a slight feeling of inferiority from the Romanians’ side, generated, most probably, by the Croats’ success in preserving their historical autonomy, with all the social and cultural consequences deriving from it. Equality between the two nations is seen only in the military field, but here, too, with specific imagological nuances. Rezumat: Note cu privire la imaginea Croaţiei şi a croaţilor la românii din Transilvania (1867-1914). Studiul îşi propune să analizeze succint modalitatea de construcţie a imaginii Croaţiei şi a croaţilor la românii din Transilvania în perioada dualistă. Deşi cetăţeni ai aceluiaşi stat, croaţii au suscitat în mediile româneşti, şi ulterior în scrisul istoric, mult mai puţin interes decât alte naţiuni din Imperiu. Acest fapt se datorează atât interacţiunii directe limitate dintre cele două corpuri etnice, cât şi situaţiei politice diferite de după 1867. Alături de descrierile geografice generale, domeniul politicii, iniţiativele social-culturale şi imaginea de popor cu atribute marţiale au reprezentat principalele coordonate ale construcţiei imagologice în presa şi manualele şcolare româneşti. Imaginea este una în general pozitivă, lăsând să se întrevadă chiar un uşor sentiment de inferioritate al românilor, generat, cel mai probabil, de succesul croaţilor în a-şi prezerva autonomia istorică, cu toate consecinţele sociale şi culturale rezultate din aceasta. Egalitatea între cele două naţiuni este reclamată doar în domeniul militar, însă şi aici cu nuanţe şi tuşe imagologice specifice. Cuvinte-cheie: Croaţia, croaţi, secolul al XIX-lea, imagologie, români, Transilvania